1985
DOI: 10.1029/jb090ib05p03649
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dislocation density on the aqueous solubility of quartz and some geologic implications: A theoretical approach

Abstract: The internal energy associated with dislocations is calculated in quartz as a function of dislocation density. These calculawhich would drive the diffusive mass transfer of SiO 2 out of the fault zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Moreover the alteration of feldspars leading to its breakdown, growth of muscovite and the loss of K into fluid was shown to be significantly important in mylonites (Knipe and Wintsch 1985). The grains of quartz and K-feldspar might be dissolved preferentially because of its high dislocation density that may increase their solubility (Wintsch and Dunning 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the alteration of feldspars leading to its breakdown, growth of muscovite and the loss of K into fluid was shown to be significantly important in mylonites (Knipe and Wintsch 1985). The grains of quartz and K-feldspar might be dissolved preferentially because of its high dislocation density that may increase their solubility (Wintsch and Dunning 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Hippertt (1994) suggested that the initial porosity is loosely connected to the preferential dissolution of quartz at sites where dislocation tangles intersect grain boundaries (cf. Wintsch and Dunning, 1985). In both the sample of this study and of Hippertt (1994), there is a clear link between the pore orientation and the bulk finite strain.…”
Section: Nucleation Of Creep Cavities During Gsi Creepmentioning
confidence: 99%
“…Fig. 28b portrays the most important contribution in pressure solution, the work W performed by the surroundings on a solid grain when a volume ΔV is moved from face 1 to face 2: and 300 MPa (Wintsch and Dunning, 1985). The range of minimum and maximum values is given.…”
Section: Driving Force Of Pressure Solutionmentioning
confidence: 99%
“…For a large enough density of dislocations, for example greater than 10 10 dislocations per cm 2 for quartz, the free energy of a crystal can be significantly increased (Table 1). The energy of a dislocation can be divided in two terms: the energy of the core of the dislocation itself, and the strain energy due to the deformation of the crystalline lattice (Wintsch and Dunning, 1985).…”
Section: Chemical Potential Of Solids In Contact With Their Solutionmentioning
confidence: 99%